Lacustrine leaf wax hydrogen isotopes indicate strong regional climate feedbacks in Beringia since the last ice age. (1st October 2021) - Daniels, W.C.; Russell, J.M.; Morrill, C.; Longo, W.M.; Giblin, A.E.; Holland-Stergar, P.; Welker, J.M.; Wen, X.; Hu, A.; Huang, Y.
Abstract: The Late-Quaternary climate of Beringia remains unresolved despite the region's role in modulating glacial-interglacial climate and as the likely conduit for human dispersal into the Americas. Here, we investigate Beringian temperature change using an ∼32, 000-year lacustrine record of leaf wax hydrogen isotope ratios (δ 2 Hwax ) from Arctic Alaska. Based on Monte Carlo iterations accounting for multiple sources of uncertainty, the reconstructed summertime temperatures were ∼3 °C colder (range: −8 to +3 °C) during the Last Glacial Maximum (LGM; 21-25 ka) than the pre-industrial era (PI; 2–0.1 ka). This ice-age summer cooling is substantially smaller than in other parts of the Arctic, reflecting altered atmospheric circulation and increased continentality which weakened glacial cooling in the region. Deglacial warming was punctuated by abrupt events that are largely synchronous with events seen in Greenland ice cores that originate in the North Atlantic but which are also controlled locally, such as by the opening of the Bering Strait between 13.4 and 11 ka. Our reconstruction, together with climate modeling experiments, indicates that Beringia responds more strongly to North Atlantic freshwater forcing under modern-day, open-Bering Strait conditions than under glacial conditions. Furthermore, a 2 °C increase (Monte Carlo range: −1 to +5 °C) over the anthropogenic era reverses a 6 °C decline (Monte Carlo range: −10 to 0 °C) through the Holocene, indicating that recent warming in Arctic Alaska has not surpassed peak Holocene summer warmth. Highlights: Alaska's climate history is evaluated using leaf wax hydrogen isotope ratios in a 32, 000 year-long lacustrine record. The record reveals mild ice-age cooling, abrupt deglacial climate events, strong Holocene cooling, and recent warming. Proxy-model comparison highlights the importance of the Bering Strait opening as a control of Beringian climate.